Advance Directives as Support of Autonomy for Persons with Dementia? A Pilot Study among Persons with Dementia and Their Informal Caregivers - Schmidhuber, Martina; Häupler, Sandra; Marinova-Schmidt, Velislava; Frewer, Andreas; Kolominsky-Rabas, Peter (Dementia and Geriatric Cognitive Disorders Extra, 2017)
Background: Advance directives could be an important instrument to support a person's will once he/she is not able to consent anymore - if composed competently. A survey was conducted to identify the level of knowledge concerning possibilities and limits of advance directives. Methods: The study was conducted as part of the Bavarian Dementia Survey (BayDem). Data were collected from January 2014 to December 2015 by structured face-to-face interviews. Study participants were persons with dementia and their informal caregivers (n = 74). Results: In total, 66% reported having written an advance directive. Concerning the participants' knowledge about possibilities and limitations of advance directives, a lack of knowledge was noted about the possibility to revoke an advance directive. Furthermore, 70% of informal caregivers and 56% of persons with dementia were not aware of the possibility to include dementia-specific terms in the advance directive. Conclusion: It is necessary to optimize structures for public information and education concerning the topic of advance directives for persons with dementia.
EVALuna2:35793
Keywords: Informal caregivers; Medical ethics; Advance directives; Dementia; Autonomy

Demenz und Ethik in der Medizin. Standards zur guten klinischen Praxis. - Frewer, Andreas; Bergemann, Lutz; Schmidhuber, Martina (Königshausen & Neumann, 2015)

Healthcare as a Human Rights Issue. Normative Profile, Conflicts and Implementation - Klotz, Sabine; Bielefeldt, Heiner; Schmidhuber, Martina; Frewer, Andreas (transcript, 2017)
This book deals with various facets of the human right to health: its normative profile as a universal right, current political and legal conflicts and contextualized implementation in different healthcare systems. The authors come from different countries and disciplines – law, political science, ethics, medicine etc. – and bring together a broad variety of academic and practical perspectives. The volume contains selected contributions of the international conference "The Right to Health - an Empty Promise?" held in September 2015 in Berlin and organized by the Emerging Field Initiative Project "Human Rights in Healthcare" (University of Erlangen-Nürnberg).
Keywords: Menschenrechte; Medizin

Menschenrechte für Personen mit Demenz. Soziale und ethische Perspektiven - Bielefeldt, Heiner; Klotz, Sabine; Schmidhuber, Martina; Frewer, Andreas (transcript, 2019)

Voluntary Refusal of Food and Fluids - Fasting to Die as a Solution at the End of Life? - Schmidhuber, Martina (Aktuelle Ernährungsmedizin, 2019)
Voluntary refusal of food and fluids, also known as fasting to die, is a controversial phenomenon in medical and nursing setting. It is a free responsible decision of a patient in ability of reason. However physicians, nurses and relatives could have an ethical problem with this decision. Sometimes this decision is connected with suicide. in the following article I will argue why fasting to die could be a decent leave from life and why fasting to die is letting die and not suicide.
CRIS-Team WoS Importer:2019-03-15